2019
DOI: 10.3390/molecules24142634
|View full text |Cite
|
Sign up to set email alerts
|

Alkene Difunctionalization Using Hypervalent Iodine Reagents: Progress and Developments in the Past Ten Years

Abstract: Hypervalent iodine reagents are of considerable relevance in organic chemistry as they can provide a complementary reaction strategy to the use of traditional transition metal chemistry. Over the past two decades, there have been an increasing number of applications including stoichiometric oxidation and catalytic asymmetric variations. This review outlines the main advances in the past 10 years in regard to alkene heterofunctionalization chemistry using achiral and chiral hypervalent iodine reagents and catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 110 publications
0
35
0
Order By: Relevance
“…Confidence in this approach stemmed from our recent vicinal and geminal difluorination of alkenes [ 26 30 ], and contemporaneous studies from the Jacobsen laboratory [ 31 34 ], under the auspices of I(I)/I(III) catalysis [ 35 37 ]. Moreover, elegant studies by Hara and co-workers have demonstrated that α-fluoroketones could be prepared by exposing silyl enol ethers to stoichiometric p -ToIIF 2 , in the presence of BF 3 ·OEt 2 and NEt 3 /HF 1:2 [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Confidence in this approach stemmed from our recent vicinal and geminal difluorination of alkenes [ 26 30 ], and contemporaneous studies from the Jacobsen laboratory [ 31 34 ], under the auspices of I(I)/I(III) catalysis [ 35 37 ]. Moreover, elegant studies by Hara and co-workers have demonstrated that α-fluoroketones could be prepared by exposing silyl enol ethers to stoichiometric p -ToIIF 2 , in the presence of BF 3 ·OEt 2 and NEt 3 /HF 1:2 [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both iodine(III) and iodine(V) compounds (also known as λ 3 -iodane and λ 5 -iodane) have been commonly used as reagents in the oxidative transformations of various simple and complex organic molecules. [12][13][14] Most importantly, the unique reactivity and oxidizing ability of λ 3 -and λ 5 -iodanes has prompted their use as efficient oxidants in variety of synthetic transformations including α-functionalization of carbonyl compounds, 15,16 oxidative rearrangements, 17,18 alkene defunctionalization 19,20 and cyclization reactions. 21,22 However, most of this transformation requires stoichiometric amounts of these reagents, generating the same molar quantity of iodoarenes as by-product thus limiting their scope.…”
Section: Introductionmentioning
confidence: 99%
“…They are non-toxic, easily prepared, stable and alternative to metal-derived oxidants/catalysts in various oxidative transformations (Yusubov and Zhdankin, 2012 ; Singh and Wirth, 2014a , b , 2017 ; Mangaonkar et al, 2018 ; Singh et al, 2018a ; Mangaonkar and Singh, 2019 ). Several research papers, book chapters and review articles have been published covering various aspects of hypervalent iodine compounds as reagents or as catalysts in α-functionalization of carbonyl compounds (Merritt and Olofsson, 2011 ; Dong et al, 2014 ), cyclizations (Singh and Wirth, 2011 , 2012 ; Singh and Mangaonkar, 2018 ; Singh et al, 2018b ), oxidative rearrangements (Singh et al, 2012 ; Singh and Wirth, 2013 ; Maertens and Canesi, 2015 ), alkene difunctionalizations (Li et al, 2018 ; Lee et al, 2019 ) and atom-transfer reactions (Li Y. et al, 2016 ). The inherent ability of hypervalent iodine reagents to act as oxidants as well as ligand transfer reagents is the key to the significant progress achieved in this area.…”
Section: Introductionmentioning
confidence: 99%